2016
DOI: 10.1038/cddis.2016.202
|View full text |Cite
|
Sign up to set email alerts
|

The pancreatitis-associated protein VMP1, a key regulator of inducible autophagy, promotes KrasG12D-mediated pancreatic cancer initiation

Abstract: Both clinical and experimental evidence have firmly established that chronic pancreatitis, in particular in the context of Kras oncogenic mutations, predisposes to pancreatic ductal adenocarcinoma (PDAC). However, the repertoire of molecular mediators of pancreatitis involved in Kras-mediated initiation of pancreatic carcinogenesis remains to be fully defined. In this study we demonstrate a novel role for vacuole membrane protein 1 (VMP1), a pancreatitis-associated protein critical for inducible autophagy, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…Autophagy is a conserved cellular process that utilizes lysosomes-mediated degradation to turn over cellular proteins or organelles. It serves as an adaptive role to remove damaged organelles and cytoplasmic aggregates against diverse pancreatic disease, including acute pancreatitis, pancreatic cancer, and CP 10 12 . Autophagy may modulate PSC remodeling in the progression from a quiescent to an activated phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is a conserved cellular process that utilizes lysosomes-mediated degradation to turn over cellular proteins or organelles. It serves as an adaptive role to remove damaged organelles and cytoplasmic aggregates against diverse pancreatic disease, including acute pancreatitis, pancreatic cancer, and CP 10 12 . Autophagy may modulate PSC remodeling in the progression from a quiescent to an activated phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Normal VMP1 protein expression is necessary to maintain normal tissue homeostasis and integ-rity. 12 At present, a large number of studies have shown that VMP1 involves the development of many tumors, including hepatocellular carcinoma, 13,14 pancreatic cancer, [15][16][17] colorectal cancer, [18][19][20] ovarian cancer, 21 and breast cancer. 22 SNP rs1295925 was located in the p53 transcriptional binding region and its mutation might affect the binding of p53 and eventually lead to different tumor susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these experiments in mice affirm our hypothesis that autophagy, induced by overexpressing VMP1 in the pancreas, significantly increases the protumor effect of the KRAS oncogene (Figure 1). In addition, we demonstrated that chloroquine, a classical inhibitor of autophagic flux (26), can reverse the effect of VMP1 overexpression on pancreatic cancer induced by the KRAS oncogene in a preclinical trial using our mouse model (25). Overall, these observations support the idea that pathways activated by pancreatitis, particularly those regulating autophagy, can promote pancreatic carcinogenesis.…”
Section: Autophagy Induced By Overexpression Of Vmp1 Enhances Transfomentioning
confidence: 95%
“…The most likely hypothesis is that autophagy induced by pancreatitis, and mediated by overexpression of VMP1, provides the energy required of cells harboring an activating mutation in the KRAS oncogene, therefore allowing their transformation. To test this hypothesis, we have recently developed an animal model wherein the genetically modified VMP1 protein is induced simultaneously with the activation of the oncogene Kras G12D specifically in the pancreas, by the addition of doxycycline to a water drink (25). This model was developed with the objective to first assess the effects of overexpressed VMP1 on initiation of pancreatic cancer, and second, to define the role of pharmacological inhibitors of autophagy in the development of pancreatic cancer.…”
Section: Autophagy Induced By Overexpression Of Vmp1 Enhances Transfomentioning
confidence: 99%
See 1 more Smart Citation